An M2L4 Molecular Capsule with a Redox Switchable Polyradical Shell. (28th October 2016) - Yazaki, Kohei; Noda, Shogo; Tanaka, Yuya; Sei, Yoshihisa; Akita, Munetaka; Yoshizawa, Michito
Abstract: Preparation of molecular nanostructures with polyradical frameworks remains a significant challenge because of the limited synthetic accessibility which is entirely different from that of neutral and ionic ones. Herein we report the quantitative formation of a new M2 L4 molecular capsule from metal ions and dihydrophenazine‐based ligands. The capsule has a spherical nanocavity (ca. 1 nm in diameter) enclosed by eight redox‐active, dihydrophenazine panels. Electrochemical oxidation of the capsule leads to the generation of multiple radical cations on the shell framework. Moreover, a stable tetra(radical cation) capsule can be reversibly obtained by chemical as well as electrochemical oxidation.